2022-RA-964-ESGO Radioguided occult lesion localisation (ROLL) for gynecologic tumor relapses: development of a technique. (20th October 2022) - Bebia, Vicente; Luzarraga, Anna; Mast, Richard; Cardozo-Saavedra, Anderson; Franco-Camps, Silvia; Pérez-Benavente, Asunción; Gil-Moreno, Antonio; Cabrera, Silvia
Abstract : Introduction/Background: Excision of peritoneal or nodal solitary lesions frequently involves performing a surgery on a previously operated area, which is more difficult to achieve with minimally-invasive approaches. Our aim was to describe the technical aspects, feasibility and complications derived from the application of the radioguided occult lesions localization (ROLL) in gynecologic oncology recurrence excision. Methodology: All consecutive patients bearing localized relapses of a gynecologic tumor that were considered candidates for surgical excision were assessed to undergo a ROLL procedure. After multidisciplinary review of images and surgical indication, patients were considered as suitable for ROLL. Injection of the relapsed tumor was performed by ultrasonography or CT guidance. Relapses were localized using a gammaprobe by minimally-invasive surgery (laparoscopic or robotic surgery) when located in the abdomen, or pecutaneously when located in the groin. Intraoperative and early (up to postoperative day 30) complications were prospectively recorded, and complications were graded according to Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 Results: A total of 8 patients underwent the procedure. Median age was 59 years (range: 35–87). Four patients had abdominal relapses, while four patients presented groin relapses. Mean operative time was 120 minutes (range: 30–190), while median estimated blood loss was 5 cc (range: 0–150 cc). All of the targeted lesions were successfully removed. No intraoperative complications were reported. One postoperative complication (inguinal lymphocele) was reported after surgery, corresponding to CTCAE grade 2 severity. Conclusion: ROLL surgery is feasible for excision of recurrences of gynecological tumors.